2010
DOI: 10.3892/ol_00000112
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-κB expression is predictive of overall survival in patients with cutaneous melanoma

Abstract: Abstract. Nuclear factor (NF)-κB is one of the most important transcription factors that plays a crucial role in the regulation of a wide spectrum of genes involved in modulating the cell cycle, apoptosis, cell growth, angiogenesis, inflammation and the tissue invasiveness of highly malignant cells. NF-κB activity has been found to be constitutively elevated in a number of human tumors from either a haematological or solid origin, such as melanomas. In several studies, NF-κB activation was shown to be an adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Thus, Abl/Arg not only affect expression, nuclear translocation, and/or activity of the transcription factors but also markedly promote their binding to cathepsin gene promoters. These data are a critical addition to understanding precisely how these transcription factors promote melanoma development, progression, and therapeutic resistance (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Finally, analysis of Oncomine and TCGA data sets revealed that the expression of Abl/Arg and SP1 or ETS1 mRNAs correlated in primary melanomas (Fig.…”
Section: Abl/arg Affect Nf-b (P65/rela) Ets1 and Sp1 Transcription F...mentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, Abl/Arg not only affect expression, nuclear translocation, and/or activity of the transcription factors but also markedly promote their binding to cathepsin gene promoters. These data are a critical addition to understanding precisely how these transcription factors promote melanoma development, progression, and therapeutic resistance (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Finally, analysis of Oncomine and TCGA data sets revealed that the expression of Abl/Arg and SP1 or ETS1 mRNAs correlated in primary melanomas (Fig.…”
Section: Abl/arg Affect Nf-b (P65/rela) Ets1 and Sp1 Transcription F...mentioning
confidence: 88%
“…Here, we found that Abl/Arg activation-induced secretion of cathepsins B and L plays a critical role in driving Abl/Arg-dependent melanoma invasion and metastasis. Moreover, our data reveal that Abl/Arg induce mRNA expression, promoter activity, and subsequent secretion of cathepsins by activating transcription factors [namely, Ets1, Sp1, and nuclear factor B (NF-B)/p65] that have well-known roles in epithelialmesenchymal transition (EMT), invasion, and therapeutic resistance (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). These data not only uncover new sig naling pathways mediated by Abl kinases, which are likely applicable to other cancers, but also support a new strategy for inhibiting secretion of cathepsins and consequently metastatic progression.…”
Section: Introductionmentioning
confidence: 95%
“…NF-κB is one of the most important transcription factors that play a crucial role in the suppression of apoptosis, as well as the induction of cell proliferation and inflammation, which is closely associated with cancer development (21)(22)(23)(24). NF-κB activation is involved in the inhibition of apoptosis by upregulating the expression of anti-apoptotic proteins, including Bcl-2, Mcl-1 and survivin (25).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is linked with the NF-κB pathway. NF-κB is a nuclear transcriptional factor that is linked to both pro-and anti-inflammatory activities [28]. In dormant cells, the NF-κB dimers are joined by inhibitory molecules, such as IκB, to keep them stable in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%